Comparison of body weight-supported treadmill training versus body weight-supported overground training in people with incomplete tetraplegia: a pilot randomized trial. (January 2015) - Senthilvelkumar, Thangavelu; Magimairaj, Henry; Fletcher, Jebaraj; Tharion, George; George, Jacob
Objective: To compare the effectiveness of body weight-supported treadmill training and body weight-supported overground training for improving gait and strength in people with traumatic incomplete tetraplegia. Design: Assessor blinded randomized trial. Setting: Rehabilitation institute of a tertiary care teaching hospital in India. Participants: Sixteen participants with traumatic motor incomplete tetraplegia and within two years of injury. Interventions: Participants were randomised to one of two groups: body weight-supported overground training on level ground and body weight-supported treadmill training. Both groups received 30 minutes of gait training per day, five days a week for eight weeks. In addition, both groups received regular rehabilitation which included flexibility, strength, balance, self care and functional training. Outcome measures: The primary outcome measure was the Walking Index for Spinal Cord Injury (/20 points) and the secondary outcome was the Lower Extremity Muscle Score (/50 points). Results: There was no statistically significant between group differences in the Walking Index for Spinal Cord Injury [mean difference=0.3points; 95% CI (-4.8 to 5.4); p=0.748] or the Lower Extremity Muscle Score [mean difference=0.2 points; 95% CI (-3.8 to 5.1); p=0.749]. Conclusions: Gait training with body weight-supported overground training is comparable to treadmill training for improving locomotion in people with traumatic incomplete tetraplegia.